DEVELOPMENT OF MULTIGRAIN HERBAL ENERGY CHOCOLATE BAR (International Journal of Food and Nutritional Sciences, 2025)
The Multigrain herbal energy chocolate bar have become papular heath conscious individuals who want a quick and convenient snacks. This study devloped a Multigrain herbal energy chocolate bar combining the benefits of Multigrains, herbal energy enhancer and dark Chocolate.Three trials formulation (T0,T1,T2,T3) varied in Multigrain herbal energy chocolate blend, and sweetner composition.sensory evaluation and nutritional analysis relvealed T2 (Protein enhanced)Profile.different